Community Based Participatory Research: A Ladder of Opportunity for Engaged Scholarship in Higher Education - Molosi-France, Keneilwe; Dipholo, Kenneth (Journal of Contemporary Issues in Education, 2022)
Higher Education the world over is recognized as a driver of development in the knowledge based economy. It is believed that Higher Education benefits the economy through the formation of human capital and building a knowledge base that contributes to solving problems in society. However, voices of frustration about graduates being unable to relate theory to practice in different contexts raises questions about the quality of teaching and learning in Higher Education Institutions (HEI). Some reports have shown that graduates seem to leave HEI’ s disengaged, ill equipped, and unable to apply acquired university knowledge to real world problems. In addition, even though the mission of the university is inclusive of engagement among others, community engagement priority seems to be emphasized only on the part of faculty members and less so on students. This in part is a result of a curriculum that mainly promotes classroom based learning and the ivory tower mentality of HEI, which places the community in the periphery of knowledge and data production. This conceptual paper argues that in order for HEI’s to produce quality graduates, who are innovative and active citizens, a transformative teaching and learning scholarship that moves beyond “classroom-based theory” is necessary, more especially for students in applied fields of study such as community development.  Borrowing from Nyerere’s educational philosophy, this paper posits that Community Based Participatory Research (CBPR), with its collaborative inquiry, social action and service learning, may provide a basis for engaged scholarship of teaching and learning that promotes engagement for higher education students in applied fields of study. Thus, by exploring the concepts of  engaged scholarship and CBPR and the nuances that exist between them, this paper seeks to underscore the importance of CBPR and how it can contribute to engaged scholarship for students.